ENGLISHES: INDONESIAN EFL TEACHERS’ PERCEPTION - Zusana E. Pudyastuti; Nurul Atma (Master Program in Linguistics, Diponegoro University, 2014)
Since English is used as a lingua franca, the growth of English users is getting bigger. The tremendous growth of English users has generated variety of English, i.e. Englishes. Such variety could affect EFL pedagogy. This paper, then, explores EFL teachers’ perception on Englishes. By employing a survey study, it is found that EFL teachers agree that it is useful for both English teachers and students to know the variety of English. However, in the teaching practice, they prefer to integrate it to other language skills and language components rather than teaching it in isolation. Besides, adopting exonormative norm, i.e. American English or British English is still used in the common teaching practice. (113) Sejak Bahasa Inggris digunakan sebagai lingua franca, pengguna bahasa Inggris semakin berkembang pesat. Perkembangan pengguna bahasa inggris tersebut telah menyebabkan variasi dalam bahasa Inggris, yaitu Englishes. Artikel ini menjelaskan tentang persepsi guru bahasa Inggris terhadap variasi tersebut. Dengan menggunakan metode survei, disimpulkan bahwa guru-guru EFL setuju bahwa pengetahuan akan Englishes sangatlah penting dimiliki baik oleh guru maupun siswa. Namun, mereka lebih menyukai jika pengajaran Englishes diintegrasikan dengan keterampilan bahasa dan komponen bahasa daripada harus mengajarkannya secara terpisah. Selain itu, menggunakan aturan exonormative, yaitu American English and British English masih tetap digunakan dalam praktik mengajar. (92)